Pushing up the magnetisation values for iron oxide nanoparticles via zinc doping: X-ray studies on the particle's sub-nano structure of different synthesis routes. Issue 36 (30th August 2016) - Szczerba, Wojciech; Żukrowski, Jan; Przybylski, Marek; Sikora, Marcin; Safonova, Olga; Shmeliov, Aleksey; Nicolosi, Valeria; Schneider, Michael; Granath, Tim; Oppmann, Maximilian; Straßer, Marion; Mandel, Karl
Abstract : We study how only slightly different synthesis approaches towards zinc doped iron oxide nanoparticles strongly influences the resulting structure and magnetisation. Abstract : The maximum magnetisation (saturation magnetisation) obtainable for iron oxide nanoparticles can be increased by doping the nanocrystals with non-magnetic elements such as zinc. Herein, we closely study how only slightly different synthesis approaches towards such doped nanoparticles strongly influence the resulting sub-nano/atomic structure. We compare two co-precipitation approaches, where we only vary the base (NaOH versus NH3 ), and a thermal decomposition route. These methods are the most commonly applied ones for synthesising doped iron oxide nanoparticles. The measurable magnetisation change upon zinc doping is about the same for all systems. However, the sub-nano structure, which we studied with Mössbauer and X-ray absorption near edge spectroscopy, differs tremendously. We found evidence that a much more complex picture has to be drawn regarding what happens upon Zn doping compared to what textbooks tell us about the mechanism. Our work demonstrates that it is crucial to study the obtained structures very precisely when "playing" with the atomic order in iron oxide nanocrystals.